The Application of Hypnosis in Sports - Li, Zhe; Li, Su-Xia (Frontiers in Psychology, 2022)
As an ancient science, hypnosis has been used by humans since the primitive societies during theocratic times. By the 20th century, scientists and psychologists had re-recognized and studied hypnosis and to explored its applications in the fields such as medicine, education, and military uses. In China, its local traditional “hypnosis” appeared in Huangdi Neijing has not received enough attention from Chinese people, and the modern hypnosis development is later than the American and European countries. Therefore, people’s understanding and applications of hypnosis remain in an inadequate state. With the development of China’s economy and the state power in the last decades, Chinese people were beginning to attach importance to the investment and development of the sports industry and realise that the psychological quality of the athletes is often a decisive factor in the success or failure of the competition. Meanwhile, hypnosis is an effective psychological training method to be used in daily training and competitions. In these cases, this essay firstly reviews the history of hypnosis, then carries out the methods of review of literature and logical analysis to explore the applications of hypnosis in sports. Thus, evidences are provided in favour of the use of hypnosis in the sports industry.